Problematika Penggunaan Generative Artificial Intelligence (AI) Pada Siswa SMK Dalam Keterampilan Menulis Pembelajaran Bahasa Indonesia - Nurillah Shalihatul Mubarokah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research is to explore the urgency of using Generative Artificial Intelligence (AI) in Indonesian language learning for vocational school students. The aim of this research is to identify whether the use of Generative AI can improve writing skills in Indonesian language material. The method used in the research is a qualitative method which is centered on an understanding and the observation techniques used. The results of the data received using this method are by holding several existing samples using 2 class samples, the first is the class with the use of AI in writing skills in learning Indonesian more with a percentage of 76.67% compared to the previous class but using the method and the same material with a gain of 28.57%. In conclusion, the use of Generative AI in learning Indonesian for vocational school students is an innovative approach that can significantly improve students' writing abilities. The research results provide concrete evidence that Generative AI technology has great potential to enrich students' learning experiences. Technological developments are very rapid in the world of education, students can easily access the availability of AI both to help in the learning process and in all existing aspects. The impact caused by the use of AI is that students are not only required to be creative in writing, but students are not willing to develop themselves with the ability to develop their ideas and ideas.